The Hell of the Subcontract: Syrian Refugees in Istanbul’s Clothing Industry - Basem Mahmud; Rosa M. Soriano-Miras (Genealogy, 2025)
This article investigates the employment conditions of Syrian refugee workers in the clothing industry in Istanbul, as well as its consequences on their socio-emotional well-being and life plans. 62 interviews in the form of life stories were conducted with these workers from workspaces of varying sizes. The research identifies ambiguity, hyper-precarity, institutional violence, and segregation (refugees mostly work in small workshops) as the main concepts for understanding these conditions. The dimensions of socio-emotional well-being are dominated by depression and loss of control over life. However, the personal (self) dimension (proud, optimistic, and staying positive with oneself) remains high. As a result, migration outside of Turkey emerges as as ongoing hope in the pursuit of stability and control over the future.